O estado do conhecimento das pesquisas sobre formação de professores no quadro da expansão da educação superior no Brasil - Bárbara Cristina Moreira Sicardi Nakayama; Douglas da Silva Tinti (EccoS – Revista Científica)
The text aims to present the state of knowledge of the Brazilian researches that deal with projects and programs developed in the context of the public policies of expansion of Higher Education and that specifically deal with teacher education. We considered the Brazilian academic productions registered in the Brazilian Digital Library of Dissertations and Theses identified from the descriptions 'expansion of higher education' and 'training of teachers' linked to all fields of search of the works. Fifteen studies were found and analyzed, and after reading the texts in full, the analytical corpus considered information about the context in which the research was developed, its objectives, theoretical references, methodologies and main results presented by the researcher. The data were systematized in synthesis tables in order to identify theoretical and methodological trends, production locus and objects of study in the interface with the presented results. The results of this work indicate a concentration of production in public universities, point out a plurality of theoretical inputs used and an emphasis on the use of documental analysis methodologies and case studies.Keywords: Knowledge State. University Expansion. Teacher Training. Institutional Policies and Programs. Introdução